2006
DOI: 10.1089/ten.2006.12.2385
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cell Proliferation and Osteogenic Differentiation in Fibrin Gelsin Vitro

Abstract: This study analyzed human mesenchymal stem cell (hMSC) behavior in a fibrin sealant. hMSC morphology, proliferation, and osteogenic differentiation were analyzed after up to 28 days of incubation in eight different formulations of fibrin gels (Tisseel) prepared with various concentrations of fibrinogen complex (FC) and thrombin. Cell morphology and distribution within the gels were observed by fluorescence microscopy after cell staining with calcein dye. Cell proliferation was assessed by measuring the fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(84 citation statements)
references
References 33 publications
8
76
0
Order By: Relevance
“…Furthermore, when fibrin is used as the matrix to encapsulate stem cells, the concentration of thrombin and fibrinogen can influence their proliferation rate and their differentiation. The results from Catelas et al [185] show that formulations containing a lower concentration of fibrinogen (5 mg ml 21 ) can support human mesenchymal stem cell growth, while a higher concentration (50 mg ml 21 ) has an increased potential for their differentiation into osteoblasts. In mammals, fibrin can degrade rapidly owing to the presence of proteolytic enzymes (fibrinolysis).…”
Section: Fibrinmentioning
confidence: 99%
“…Furthermore, when fibrin is used as the matrix to encapsulate stem cells, the concentration of thrombin and fibrinogen can influence their proliferation rate and their differentiation. The results from Catelas et al [185] show that formulations containing a lower concentration of fibrinogen (5 mg ml 21 ) can support human mesenchymal stem cell growth, while a higher concentration (50 mg ml 21 ) has an increased potential for their differentiation into osteoblasts. In mammals, fibrin can degrade rapidly owing to the presence of proteolytic enzymes (fibrinolysis).…”
Section: Fibrinmentioning
confidence: 99%
“…Thrombin buffer solution, on the other hand, contains calcium and sodium chlorides. High fibrinogen, and to a lesser extent low thrombin, concentrations have been shown to reduce the proliferation of human MSCs [7][8][9] and dermal fibroblasts [3]. The fibrinogen concentration thresholds determined by these studies, however, varied from 18 to 50 mg/mL fibrinogen.…”
Section: Introductionmentioning
confidence: 83%
“…Scaffolds leading to better cell proliferation are not necessarily more appropriate for cell differentiation as illustrated by the study of Catelas et al [8]. They showed that high-fibrinogen content, though lowering cell proliferation rates, improved osteogenic differentiation of human BMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We filled the canal space with fibrin gel, which acts as a scaffold for immigrating cells [37]. The selection of the scaffold in the cleaned and disinfected pulp space is also considered to be essential for the success of tissue engineering in the current context [8,11,38].…”
Section: Discussionmentioning
confidence: 99%